The Student’s Reflective-Inquiry Competencies on Problem Solving - Mohammad Imam Farisi; Dwi Sambada; Teguh Prakoso (Intelektual Pustaka Media Utama, 2017)
This study describes student’s reflective-inquiry competencies on problem solving at Tuton assignments, majoring Curriculum and Materials of Citizenship Education (PKNI 4313). This study is conducted in two Tuton periods, 2015.1 and 2015.2 by using four stages of Research and Development. As the research subject, this study is involving 39 student participants. The reflective-inquiry contents are presented in real social or public problems, cases or issues, which give any challenge to the student to think by reflective-inquiry. The student’s reflective-inquiry competency is collected by Practical Inquiry Model instrument is used to assess the student’s cognitive, social, and teaching presence in the online learning context or computer conference. Generally, results of the study shown that student’s reflective-inquiry competency in the problem solving at Tuton assignments are “not satisfy” especially in the steps : (1) reflective-inquiry process, such as the ability of reviewing, examining, exploring, or analyzing all the consideration to reach the explication and clarification from the problem; building the relation of valuable linkages and finding the possibility explication; (2) reflective-inquiry post, such as the ability in making resolution or conclusion; and taking a projected decision that they have been clarified, combined, or solved.